Anodic oxidant, oxidation process and oxidation film for gas diffuser

By using anodizing agents and processes with components such as oxalic acid, citric acid and polyethylene glycol, the adsorption and drop of particles caused by the large diameter of the anodized film are solved, and the formation of oxide films with high heat resistance, corrosion resistance and insulation properties is achieved.

CN115772697BActive Publication Date: 2025-03-18HEFEI WEIRUI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210881563.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-26
Publication Date
2025-03-18
Estimated Expiration
2042-07-26

AI Technical Summary

Technical Problem

In the prior art, the membrane micropores produced by anodizing have large diameters, which easily adsorb fine particles in the air, causing expansion and fall of the inner surface of the cavity, and the film has insufficient heat resistance, corrosion resistance, insulation and uniformity.

Method used

Oxalic acid is used as the main medicine solution, citric acid and polyethylene glycol are used as additives to generate an oxide film through the anodizing process, controlling the anodizing voltage and time, and ensuring the uniformity and thickness of the film.

Benefits of technology

The resulting oxide film has good heat resistance, corrosion resistance, insulation and uniform film thickness, reducing the generation of particles in the film and ensuring product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115772697B_ABST
    Figure CN115772697B_ABST
Patent Text Reader

Abstract

The present invention discloses an anodic oxidant, oxidation process and oxide film applied to a gas diffuser, belonging to the field of LCD technology. The present invention adopts 5% oxalic acid as the main electrolyte to reduce the dissolution rate of the film in an acidic electrolyte environment, and at the same time obtains a thicker barrier layer; 1% citric acid blocks the pores through the macromolecular complex formed by the "complexation effect", thereby increasing the corrosion resistance of the film; 2% polyethylene glycol can improve the dispersion ability of the electrolyte, expand the current density range, and enhance the polarization effect of the cathode, thereby obtaining an excellent electrical performance film. The thickness of the anodic oxide film is greater than 2.9mm, the standard deviation is less than 0.1mm, the withstand voltage is greater than 240V, and the impedance is greater than 630Ω.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of LCD technology, and more specifically to an anode oxidant, an oxidation process and an oxidation film applied to a gas diffuser. Background Art

[0002] LCD (Liquid Crystal Display) is the abbreviation of Liquid Crystal Display, and TFT-LCD (Thin Film Transistor Liquid Crystal Display) technology is a technology that cleverly combines microelectronics technology with liquid crystal display technology. People use the PECVD process to inject the required GAS state into the vacuum chamber (cavity), use RF POWER to decompose GAS into Plasma (plasma) state, and evaporate it on the GLASS to form a-Si / n+a-Si semiconductor film or SiN insulation film.

[0003] Then, a tiny shape - the TFT structure - is etched out through the ETCH process. In TFT LCD, the function of TFT is equivalent to a switch. The TFT array is processed on large-size glass, and then the array substrate is bonded to another substrate with a color filter film, and liquid crystal is injected in the middle. After post-processes such as polarizer lamination, a liquid crystal display is finally formed.

[0004] With the improvement of people's living standards and demands, the TFT-LCD industry has developed rapidly in China in recent years, and LCD screens have tended to develop in larger sizes. Currently, the maximum size has been updated to 10.5G, which can economically cut 60-70-inch LCD panels.

[0005] The manufacturing process of TFT-LCD is complex, among which PECVD (plasma enhanced chemical vapor deposition) is a key step. The deposition equipment used is mainly for film formation on glass (glass substrate).

[0006] CVD equipment is mainly composed of various chambers, and CVD PARTS (components of CVD equipment) are scattered throughout the chambers, mainly composed of Backing Plate (BP for short), Diffuser (DF for short), Susceptor (SS for short) and other components, and different components have different functions.

[0007] In recent years, with the advancement of manufacturing technology, the size of LCDs has become larger and larger, from the initial 2nd, 5th, and 6th generations to the current 8.5th and 10.5th generations, and the corresponding equipment and spare parts sizes have also increased generation by generation.

[0008] The original diffuser did not need anodizing treatment. The bare aluminum surface was cleaned and applied to the chamber. However, the power of the reaction in the chamber of the 10.5G large-generation line is high, and the bare diffuser surface has no insulation. During the production process, the production of the coating also gives the diffuser surface a certain degree of insulation, especially in the early stage of CC. This situation will cause the thickness of the coating on the glass surface of different batches to be uneven. It was not until recent years that a new anodizing process was proposed: Diffuser is anodized to increase its surface insulation, which completely solved this problem.

[0009] Because the diffuser is in a high temperature, high pressure, corrosive gas environment in the chamber, especially the general temperature is in the range of 300-400 degrees, and some processes even reach 450 degrees. In such an environment, the film performance required must have high heat resistance, high uniformity and corrosion resistance. The key indicator parameters for evaluating the diffuser film are here.

[0010] Japanese and Korean companies and domestic existing processes all use phosphoric acid as the matrix as the electrolyte for anodizing, which has the advantages of uniform film formation rate, high barrier layer thickness and good impedance.

[0011] Under this process condition, a film with a thickness of 2 to 5 microns can be produced. The barrier layer thickness is about 100 nm under SEM observation. The film has good uniformity, insulation performance, corrosion resistance, heat resistance and other properties.

[0012] General Phosphoric Acid Coating Process Parameters Table

[0013] Electrolyte temperature Power supply type Final voltage Anode time 3%~5%H3PO4+dispersant 30℃ Voltage stabilization process 85V 60min

[0014] The membrane produced using phosphoric acid is generally used as the middle layer of the composite membrane. The diameter of the membrane's micropores is more than 10 times larger than that of other membranes, and it has good adsorption and binding capabilities for the coating layer.

[0015]

[0016] Since the pore diameter of the phosphoric acid membrane is large, it is easy to absorb particles in the air during production and inspection, so the inner surface of the chamber expands and particles fall off. Summary of the invention

[0017] 1. Technical problem to be solved by the invention

[0018] In view of the large diameter of the micropores in the film produced by the current anodizing, particles in the air are easily adsorbed during the production and inspection process, resulting in expansion and falling of the inner surface of the cavity. The present invention provides an anodizing agent, an oxidation process and an oxide film for use in a gas diffuser. The generated oxide film has good heat resistance, corrosion resistance, insulation and uniform film thickness, reduces the generation of particles in the film, and ensures product quality.

[0019] 2. Technical solution

[0020] In order to achieve the above object, the technical solution provided by the present invention is:

[0021] The anode oxidant of the gas diffuser of the present invention is characterized by comprising a main liquid with a mass fraction of 3%-8%, a main additive with a mass fraction of 0.5%-2%, and a secondary additive with a mass fraction of 0%-2%.

[0022] Furthermore, the main drug liquid is oxalic acid, the main additive is citric acid, and the secondary additive is tartaric acid or polyethylene glycol.

[0023] Furthermore, the mass fraction of oxalic acid is 5%, the mass fraction of citric acid is 1%, and the mass fraction of polyethylene glycol is 2%.

[0024] On the other hand, the mass fraction of the oxalic acid is 5%, the mass fraction of the citric acid is 1%, and the mass fraction of the tartaric acid is 2%.

[0025] An anodizing process for a gas diffuser of the present invention is characterized in that the steps are:

[0026] Step 1: Remove the surface cutting fluid and processing oil from the gas diffuser in a weak alkaline degreasing liquid at a temperature of 55°C;

[0027] Step 2: Use a fully automatic grinding robot to grind the surface of the gas diffuser to remove surface scratches and mask the non-anode area.

[0028] Step 3: Use a sandblasting robot to sandblast the product surface to achieve the roughness requirements required by the customer;

[0029] Step 4: Place the gas diffuser in a degreasing, water washing, etching, water washing, purification, and water washing tank in sequence, perform chemical polishing, and then perform automatic high-pressure water washing;

[0030] Step 5, placing the gas diffuser in a specific anodizing electrolyte tank for anode;

[0031] Step 6: Wash and dry the gas diffuser after the anode

[0032] Step 7: Perform appearance inspection and performance test on the anodized product.

[0033] Furthermore, in the step 5, the aluminum plate is placed in an anodizing agent, the anodizing voltage is controlled to be 55V, the anodizing time is 40min, and the temperature is 15°C-20°C.

[0034] Furthermore, in the step seven, the oxide film is subjected to a withstand voltage impedance test, a cutting test, and a surface SEM test.

[0035] The anodized film of a gas diffuser of the present invention is characterized in that the anodized film has a thickness greater than 2.9 mm, a standard deviation less than 0.1 mm, a withstand voltage greater than 240 V, and an impedance greater than 630 Ω.

[0036] 3. Beneficial effects

[0037] Compared with the existing known technologies, the technical solution provided by the present invention has the following significant effects:

[0038] (1) The anode oxidant of a gas diffuser of the present invention uses oxalic acid as the main agent, which can reduce the porosity of the film and reduce the pore size during the anodization process. At the same time, by adding citric acid, the generation rate of the film is increased, the uniformity of the film is improved, the adsorption of particles is reduced, and the problem of falling due to expansion of the surface of the cavity is avoided.

[0039] (2) The anode oxidant of a gas diffuser of the present invention is prepared by adding a secondary additive, polyethylene glycol, into the main solution. The polyethylene glycol has a uniform dispersion effect, thereby increasing the film formation rate and shortening the anode operation time.

[0040] (3) The anodizing process of a gas diffuser of the present invention controls the process during the anodizing process, improves the initial voltage through the voltage stabilization process, controls the anodizing voltage to 55V, and adopts a step-by-step voltage increase method. While ensuring the uniformity of the film, a thicker barrier layer can be obtained, thereby improving the insulation performance of the film.

[0041] (4) The anodized film of a gas diffuser of the present invention uses oxalic acid + organic acid to adjust the pore size of the film, increase corrosion resistance, and reduce the PT incidence rate; using the test piece characterization method, products that are difficult to measure the film can be measured non-destructively. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The current-time curve (a) when the porous anodic oxide film is generated and the structural change of the anodic oxide film in the corresponding area (b) are shown;

[0043] Figure 2 It is a graph showing the change of current and voltage over time in the present invention;

[0044] Figure 3 This is a diagram for setting specific parameters of the voltage stabilization process in the present invention;

[0045] Figure 4 This is an enlarged view of the membrane structure of the novel drug of the present invention after thermal shock;

[0046] Figure 5 This is a thermal shock process diagram of the present invention;

[0047] Figure 6 This is a SEM analysis diagram of the membrane surface of the present invention. DETAILED DESCRIPTION

[0048] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with the accompanying drawings and embodiments.

[0049] The anode oxidant of a gas diffuser of the present invention comprises a main liquid with a mass fraction of 3%-8%, a main additive with a mass fraction of 0.5%-2%, and a secondary additive with a mass fraction of 0%-2%, wherein the main liquid is oxalic acid, the main additive is citric acid, and the secondary additive is tartaric acid or polyethylene glycol.

[0050] Example

[0051] Generally, in order to obtain high withstand voltage performance, it is necessary to produce a barrier-type oxide film with a high barrier layer thickness. Inorganic acids such as boric acid and silicic acid can be used as electrolytes for the formation of barrier-type films, but they are not used due to problems such as handling and the environment.

[0052] Oxalic acid is used as the electrolyte, and the barrier layer of the anode film is about 20nm thinner than that of phosphoric acid. At this time, adding some large molecular weight organic acids as additives can slow down the dissolution rate of the film, effectively shrink the pore size, improve corrosion resistance and uniformity. To this end, this embodiment is improved from the aspect of liquid preparation:

[0053] Since there are many types of additives and the concentration has a great influence, if a comprehensive comparison is used, the number of experiments will be too many. In order to explore the best experimental conditions, a simple comparison method is used, that is, a method of fixing one factor and changing other factors. The experimental conditions are shown in Table 1.

[0054] In this embodiment, the existing anode oxidant generally uses phosphoric acid as the main liquid, and the final voltage is 85V, the anode time is 120min, and the temperature is controlled at 30°C. However, the inventor found that after using oxalic acid as the main liquid, if the original process is still used, the performance of the oxide film will be reduced, which does not meet the purpose of improving the effect of the oxide film. Therefore, the inventor improved the experimental conditions. Combined with Figure 1, ab segment is the initial stage of anodization, the barrier layer is generated, the resistance increases, and the current decreases rapidly; bc segment is the oxide film corroded and dissolved in the acidic electrolyte environment, the resistance decreases, and the current increases; d segment is the oxide film growth rate and dissolution rate reach a balance, the current is stable, and the thickness continues to grow. It can be found that when the electrolyte composition is changed, the thickness of the membrane barrier layer is not much different from the phosphoric acid method (the main influencing factor is the initial voltage). After adding citric acid, the pore size of the membrane micropores can be significantly shrunk, and the addition of the secondary additive polyethylene glycol can reduce the anode time. Finally, when the final voltage is 55V, it can achieve better results without causing energy waste.

[0055] Table 1 Anodic oxidant composition and experimental conditions

[0056]

[0057] In order to control the thickness of the anodized film, it is necessary to control the anodizing time: the basic point of the process management of the thickness of the aluminum anodized film is current density × oxidation time. Therefore, the thickness of the anodized film (um) = current density (A / dm 2 ) × oxidation time (min) × F, where F is generally 0.3. This embodiment uses oxalic acid as the main liquid, so F is 0.2. This embodiment determines the final voltage and combines Figure 2 , determine the appropriate current density, and finally determine that when the anodizing time is 40 minutes, the appropriate film thickness can be obtained and the uniformity of the oxide film can be guaranteed.

[0058] The anodizing process of a gas diffuser of this embodiment comprises the following steps:

[0059] Step 1: Remove the surface blood and processing oil of the gas diffuser in a weak alkaline degreasing liquid at a temperature of 55°C;

[0060] Step 2: Use a fully automatic grinding robot to grind the surface of the gas diffuser to remove surface scratches and mask the non-anode area.

[0061] Step 3: Use a sandblasting robot to sandblast the product surface to achieve the roughness requirements required by the customer;

[0062] Step 4: Place the gas diffuser in a degreasing, water washing, etching, water washing, purification, and water washing tank in sequence, perform chemical polishing, and then perform automatic high-pressure water washing;

[0063] Step 5, placing the gas diffuser in a specific anodizing electrolyte tank for anode;

[0064] Step 6: Wash and dry the gas diffuser after the anode

[0065] Step 7: Perform appearance inspection and performance test on the anodized product.

[0066] The oxide film was subjected to voltage resistance test, cutting test and surface SEM test respectively. The thickness of the anodized film was greater than 2.9 mm, the standard deviation was less than 0.1 mm, the voltage resistance was greater than 240 V, the impedance was greater than 630 Ω, and the SEM test aperture was 6-12 nm (see Figure 6 ).

[0067] In step 3, the aluminum plate is anodized using the conditions in Table 1. It is worth noting that this embodiment uses a step-by-step voltage control process to increase the voltage over time, rather than directly applying the maximum voltage. Since there are many holes on the surface of the product, the surface area reaches 7362dm 2 According to the steady current process, the current density is 1A / dm 2 , the total current will exceed the maximum range of the rectifier (5000A). If the current stabilization process is used for large-size products, the film forming speed in different areas of the product will be different due to the different contact currents in the center area and the surrounding areas, which will lead to uneven film thickness. Therefore, this embodiment applies different voltages at different times and gradually increases the voltage to obtain a uniform film thickness. At the same time, the initial voltage is set to 12V, which increases the thickness of the barrier film. For specific setting parameters of the voltage stabilization process, see Figure 3 .

[0068] After experiments on the groups in Table 1, it was found that group B2 was the best. Adding auxiliary additives to B2 gave better film performance B2f.

[0069] Table 2B2 Group Additives Composition

[0070]

[0071] Performance parameters show that adding 1% citric acid and 2% polyethylene glycol to 5% oxalic acid can significantly improve the voltage resistance and impedance performance of the film after anode.

[0072] Table 3 Performance parameters of the film after adding organic acid

[0073]

[0074] Combination Figure 4 and Figure 5 The film was tested. During the experiment, the film was subjected to a thermal shock test and maintained at 400°C for 30 minutes (11 times). The SPEC was ≥ 6 times. It was found that no cracks were generated in the film after 11 thermal shocks, which met the thermal shock performance requirements.

[0075] The corrosion resistance test was carried out on group B2. The specific parameters are shown in Table 4.

[0076] Table 4 Corrosion resistance test table

[0077]

[0078] Table 5 Comparison of properties of phosphoric acid film and new agent film

[0079]

[0080] Table 6 Comparison of film thickness and uniformity of phosphoric acid film and new agent film

[0081]

[0082] Table 7 Comparison of the thickness formation rate of phosphoric acid film and new agent film

[0083]

[0084] Referring to Table 5-7, the film thickness and uniformity produced by the new drug are better than those of the original drug.

[0085] The results of the above instrument tests are as follows:

[0086] 1. The new drug has a higher film formation rate and a shorter oxidation time;

[0087] 2. The voltage resistance per unit film thickness is better;

[0088] 3. Impedance performance is not much different from the original;

[0089] 4. The corrosion resistance and heat resistance are similar and can meet customer needs;

[0090] 5. The pore size of the membrane is much smaller than the original membrane;

[0091] In summary, through the above series of improvements:

[0092] A new type of anodizing solution (5% oxalic acid + 1% citric acid + 2% polyethylene glycol) was used to make corresponding improvements to the hangers. After automatic high-pressure cleaning, the products shipped out were finally verified by the client and performed well. This improvement was ultimately successful.

[0093] In summary, 5% oxalic acid is used as the main electrolyte to reduce the dissolution rate of the film in an acidic electrolyte environment and obtain a thicker barrier layer; 1% citric acid blocks the pores through the macromolecular complex formed by the "complexation effect", thereby increasing the corrosion resistance of the membrane; 2% polyethylene glycol can improve the dispersion ability of the electrolyte, expand the current density range, and enhance the polarization effect of the cathode, thereby obtaining a film with excellent electrical properties.

[0094] The present invention and its embodiments are described schematically above, and the description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and designs a structural method and an embodiment similar to the technical solution without creativity without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. An anode oxidant for a gas diffuser, characterized in that: It comprises a main liquid medicine, a main additive and a secondary additive, wherein the main liquid medicine is oxalic acid, the main additive is citric acid, and the secondary additive is polyethylene glycol; the mass fraction of the oxalic acid is 5%, the mass fraction of the citric acid is 1%, and the mass fraction of the polyethylene glycol is 2%; and the gas diffuser is an aluminum plate.

2. An anodic oxidation process for a gas diffuser using the oxidant according to claim 1, characterized in that: The steps are: Step 1: using degreasing liquid to remove cutting fluid and processing oil from the surface of the gas diffuser; Step 2: Grind the surface of the gas diffuser to remove scratches and shield the non-anode area; Step 3: sandblast the surface of the gas diffuser to meet certain roughness requirements; Step 4: Place the gas diffuser in a degreasing, water washing, etching, water washing, purification, and water washing tank in sequence, perform chemical polishing, and then perform high-pressure water washing; Step 5: placing the gas diffuser in an anodic oxidant for anodization; the final anodization voltage is controlled at 55V, the anodization time is 40min, and the temperature is 15°C-20°C; Step 6, washing and drying the anodized gas diffuser; Step 7: Perform appearance inspection and performance test on the anodized product; In the step 5, the voltage control adopts a step-by-step voltage boosting process, and the voltage increases gradually over time.

3. The anodizing process for a gas diffuser according to claim 2, characterized in that: In the step 5, the initial voltage of the anodization is controlled to be 12V.

4. The anodizing process for a gas diffuser according to claim 3, characterized in that: In the step seven, the oxide film is subjected to a withstand voltage impedance test, a cutting test, and a surface SEM test.

Citation Information

Patent Citations

  • Metal component and manufacturing method thereof and process chamber having the metal component

    CN107604342A

  • KR20210052756A